IMPLEMENTASI KEBIJAKAN BUMD BANK PAPUA UNTUK PENINGKATAN PENDAPATAN ASLI DAERAH PROVINSI PAPUA - Mustakim, Mustakim; Asnawi , Meinarni; Aedah, Nur (JURNAL KEBIJAKAN PUBLIK, 2024)
This research aims to examine and analyze the Implementation of Regional Owned Enterprise Policy in Increasing Original Regional Income in Papua Province. As well as reviewing and analyzing supporting and inhibiting factors for the implementation of Regional Owned Enterprise Policy in Increasing Original Regional Income in Papua Province. This research is important to optimize the role of BUMDs such as PT. Bank Papua in increasing Papua's Original Revenue for sustainable development. This research uses a qualitative research approach with the research location at PT. Bank Papua Papua Province. Data collection techniques are observation, interviews and documentation. Data analysis techniques are data reduction, data presentation, and drawing conclusions. The results of this research show that the implementation of the Regional Owned Enterprise Policy in Increasing Original Regional Income in Papua Province, researchers found that, Communication, implemented by the Papua regional government, can have a positive impact. Resources, adjust the amount of funds available or implement according to the amount of funds available. Disposition, source of income so that it can cause less than maximum results. Bureaucratic structure, agencies have obligations and responsibilities, and everything is carried out well by stakeholders as users. Supporting and Inhibiting Factors for Implementing Regional Owned Enterprise Policy in Increasing Original Regional Income in Papua Province, researchers found that, Internal factors, regional income from optimization efforts to extract large sources of income with good management. External factors, minimal control and supervision from PT. Papua Bank.